2012
DOI: 10.1152/japplphysiol.01480.2010
|View full text |Cite
|
Sign up to set email alerts
|

o2 on-kinetics in isolated canine muscle in situ during slowed convective O2 delivery

Abstract: Goodwin ML, Hernández A, Lai N, Cabrera ME, Gladden LB. VȮ2 on-kinetics in isolated canine muscle in situ during slowed convective O2 delivery. J Appl Physiol 112: 9 -19, 2012. First published October 6, 2011 doi:10.1152/japplphysiol.01480.2010.-The purpose of this study was to examine O2 uptake (V O2) on-kinetics when the spontaneous blood flow (and therefore O2 delivery) onresponse was slowed by 25 and 50 s. The isolated gastrocnemius muscle complex (GS) in situ was studied in six anesthetized dogs during tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The mechanism of this delayed response remains unclear, but interventions designed to limit the transport of O 2 generally slow kinetics [e.g. β blockade (Hughson & Smyth, 1983), supine exercise (Hughson et al 1991) or slowed pump perfusion (Goodwin et al 2011)]. This expected response formed an integral part of our experimental design, because it allowed us to assess the subsequent relationship amongst slowed kinetics and absolute [HHb] and its spatial heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of this delayed response remains unclear, but interventions designed to limit the transport of O 2 generally slow kinetics [e.g. β blockade (Hughson & Smyth, 1983), supine exercise (Hughson et al 1991) or slowed pump perfusion (Goodwin et al 2011)]. This expected response formed an integral part of our experimental design, because it allowed us to assess the subsequent relationship amongst slowed kinetics and absolute [HHb] and its spatial heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals manifesting slowed phase II pulmonary O 2 uptake () kinetics (τ) demonstrate a large, transient ‘overshoot’ in the deoxygenation response at the onset of exercise (Bauer et al 2007; Sperandio et al 2009, 2012; Porcelli et al 2010; Barbosa et al 2011; Bowen et al 2012); a feature that is attenuated or absent in individuals with more rapid kinetics (DeLorey et al 2003; Grassi et al 2003; Sperandio et al 2009; Porcelli et al 2010). Where kinetics are experimentally slowed in the isolated canine hindlimb, the HHb overshoot is increased and kinetics are slowed (Goodwin et al 2011). In addition, the intervention of warm‐up exercise (Bowen et al 2012) and the administration of sildenafil (Sperandio et al 2012) acutely speeded kinetics in chronic heart failure (CHF) patients, and this was associated with a reduction in the HHb overshoot, thus suggesting that a faster adjustment of microvascular O 2 delivery relative to demand may relieve an O 2 delivery limitation to in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This response has been explained on the basis of deep muscle containing proportionally more slowtwitch (type I) muscle fibers with a greater sensitivity of vasodilatory control (2,28). Goodwin et al (14) used NIRS directly on the surface of canine hindlimb muscles to access both superficial and deep muscle deoxygenation during stimulated contractions. They showed that slowed blood flow speeded the rate of muscle deoxygenation during the transition from rest to steady state.…”
mentioning
confidence: 99%
“…The partial pressure of O 2 in the interstitial space (P ISF O 2 ), which is dissociated from red blood cell (RBC) hemoglobin and free to diffuse to intracellular mitochondrial sinks without appreciable interference from myoglobin desaturation, is sensitive to rapid changes in the balance between supply and demand. Different approaches ranging from whole animals (Hoyt, Wickler et al 2006, Rodrigues, Figueroa et al 2007), isolated muscles (Goodwin, Hernandez et al 2012); (McDonough, Behnke et al 2005), to single fibers (Hogan 2001); (Kindig, Howlett et al 2003); (Wust, van der Laarse et al 2013) have sought to characterize the relationship of the partial pressure of O 2 (PO 2 ) and VO 2 . The description of P ISF O 2 supply/demand coupling for intact muscle preparations in vivo , however, remains incomplete.…”
Section: Introductionmentioning
confidence: 99%